Internal communication and job performance in Peruvian health professionals during the COVID-19 pandemic - Jorge Luis Damián Foronda; Ericson Félix Castillo Saavedra; Cecilia Elizabeth Reyes Alfaro; Rosa María Salas Sánchez; Carmen Isolina Ayala Jara (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Background: Rationale: Internal communication within an organization ensures that workers carry out their activities effectively; which, in the health context, translates into prioritizing the patients´ well-being and quality of life. Objective: to determine the relationship between internal communication and job performance in Peruvian health professionals during the COVID-19 pandemic. Methods: descriptive correlational study, carried out with the participation of 100 professionals from the maternal-infant department of a public hospital in Chimbote, Peru. Two data collection instruments were applied using online Google questionnaires, corresponding to the variables internal communication and job performance. The information was recorded and processed through descriptive statistics, through frequencies and percentages. The Statistical Package for the Social Sciences program version 26 was used, and a reliability of 95% was considered for Pearson's bivariate correlation. Results: the work performance of the maternal and child department professionals showed a high level (51%), and that of internal communication was medium (57%). In the analysis by dimensions, a direct and significant relationship was found between descending and job performance, as well as between responsibility and internal communication. Conclusion: the level of internal communication was medium, adequate with respect to the COVID-19 pandemic situation, and was directly and significantly related to job performance in the Peruvian health professionals who participated in the study.